Scribal tools in ancient Israel: a study of biblical Hebrew terms for writing materials and implements - Zhakevich, Philip (History, Archaeology, and Culture of the Levant, 2021)
Frontmatter -- Contents -- Figures and Tables -- Acknowledgments -- Abbreviations -- Chapter 1. Introduction -- Chapter 2. Papyrus -- Chapter 3. Stone and Plaster -- Chapter 4. Skins, Scrolls, Tablets, Ostraca, and Uncommon Writing Surfaces -- Chapter 5. Scribal Instruments and Glyptics -- Chapter 6. Egypt’s Influence on Canaan and Ancient Israel -- Chapter 7. Conclusion -- Works Cited -- Ancient Sources Index -- Subject Index